Method for testing silicon content in silicon-carbon material
By forming a preoxidized layer on the surface of silicon carbon material and performing two-stage burning of gradient temperature, the problem of high time and cost of testing silicon content in silicon carbon materials in the prior art is solved, and a fast, accurate and safe test effect is achieved.
Patent Information
- Application Number
- CN202411906282.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
AI Technical Summary
There is a lack of a method in the prior art that can accurately, quickly and at low cost to test the silicon element content in silicon-carbon composites, resulting in the inability to meet the needs of rapid response and large-scale testing in industrial production.
The pre-oxidation layer is formed by using an oxidizing solvent on the surface of the silicon carbon material and performing two-stage burning of gradient temperature in the heating device to generate oxides, thereby quickly and accurately determining the silicon content.
This method reduces testing time and cost, improves the testing efficiency of Si content in silicon-carbon materials, and provides a method with shorter testing cycles, higher stability and higher safety.
Smart Images

Figure CN119643360A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicon-carbon materials, and in particular to a method for testing silicon content in a silicon-carbon material. Background Art
[0002] At present, there are several main testing methods for testing the Si content in silicon-carbon composites: the first is based on the TG (thermogravimetric analysis) method for characterizing silicon-carbon in the preparation of micro-nano porous silicon / carbon composite materials and research on their performance as negative electrode materials for lithium-ion batteries (2020); the second is the weight method. The national standard GB / T38823-2020 Silicon Carbon discloses a high-temperature calcination weight method, and CN111122373A discloses a method for testing the silicon content by calcination after acidification and heating; the third is based on the YS / T1509.1-2021 ICP trace element analysis method.
[0003] Among them, the TG method and the TG analysis method mainly calculate the silicon content through the weight loss phenomenon of the sample at high temperature; the high-temperature burning weight method disclosed in the national standard GB / T38823-2020 mainly removes carbon by increasing the temperature to 1200°C and burning silicon-carbon powder for a long time. Although this method is simple, the long high-temperature burning time causes excessive oxidation of silicon, which increases the test error after burning, and requires a longer constant weight time to stabilize the mass error after burning at 0.3mg. The weight method disclosed in CN111122373A is to calculate the silicon content based on the mass after high-temperature heating and burning after acid treatment; the method of trace element analysis by ICP spectroscopy is based on the removal of carbon at high temperature, melting with alkali, and digesting the melt with acid. The melt is converted into insoluble silicic acid by adding acid, and then hydrofluoric acid is added to volatilize silicon tetrafluoride and remove it, and then test the free Si content. The sum of the silicon content calculated by the mass method and the free silicon content tested by the ICP method characterizes the total silicon content.
[0004] Among the above test methods, the method based on TG analysis is simple to operate, but the single sample test takes a short time, is costly, and cannot test multiple samples simultaneously. It cannot meet the needs of large-scale sample testing in actual industrial production, which brings great challenges in large-scale production and quality control, and cannot meet the needs of rapid response in the industrial production process. Based on the high temperature burning weight method in the national standard, the sample is burned at 1200℃ for 8h in a box furnace or atmosphere furnace, and then the sample is weighed at high temperature. This method is simple to operate and can be used for batch sample testing, but the burning temperature is high, the burning time and subsequent constant weight time are long, the test efficiency is low, and it cannot meet the needs of rapid response of industrial production; based on the acidification weight method disclosed in the CN111122373A method, the sample is first acidified and then burned on the basis of the method provided by the national standard. Although the burning time is reduced, it is easy to cause industrial accidents because highly dangerous acids such as hydrofluoric acid are used in the pretreatment; The trace element testing method based on ICP spectroscopy also requires the use of hydrofluoric acid and the acidified sample must be carbonized at high temperature before digestion. The Si metal element is a difficult-to-digest element, which can easily lead to incomplete digestion and have a great impact on the free silicon test error. Although the samples can be tested in batches, the testing method requires carbonization after heated acid treatment and then digestion and constant volume testing of free silicon content and high-temperature burning after acidification to test silicon content. The test time is long and the test cost is high, and it cannot meet the rapid response testing needs of batch samples in actual production.
[0005] The existing national standard method has a long test cycle and a high test temperature, which has high requirements for equipment. The TG method has a short test cycle and high accuracy, but cannot be used for batch testing. It is more suitable for research and development verification. In the trace metal element test method, after the silicon-carbon material is carbonized, hydrofluoric acid needs to be used to digest the Si in the silicon-carbon material. Acid solvents are highly dangerous, and the use of hydrofluoric acid causes a large loss of ICP spectrometer accessories. At high concentrations, hydrofluoric acid is easy to damage optical instrument components, which is not conducive to industrial rapid batch testing. There is no new method in the prior art that can accurately, quickly, and low-costly test the content of silicon in silicon-carbon composite materials.
[0006] Therefore, the existing technology needs to be improved. Summary of the invention
[0007] There is no new method in the prior art that can accurately, quickly and at low cost test the silicon content in silicon-carbon composite materials. Therefore, the present invention provides a method for testing the silicon content in silicon-carbon materials to solve the above problem.
[0008] To achieve the above object, the present invention provides a method for testing the silicon content in a silicon-carbon material, which specifically comprises the following steps: S1. Provide a silicon-carbon material, perform pretreatment, mix an oxidizing solvent on the surface of the silicon-carbon material, coat an oxide layer, and obtain a material to be tested; S2, transferring the material to be tested into a crucible, placing the crucible into a heating device at room temperature, and setting a gradient temperature for the first stage of burning; S3, transferring the heated crucible to a dryer, cooling it to room temperature and weighing it; S4. Re-burn the crucible and the material to be tested after the burning in the second stage, so that the material to be tested is in a constant weight state, and the silicon content in the silicon-carbon material is calculated by weighing the result.
[0009] In one implementation, in S1, the oxidizing solvent includes any one of hydrogen peroxide, sodium hypochlorite and iodine.
[0010] In one implementation, in S2, the heating device is a muffle furnace or a box-type atmosphere furnace.
[0011] In one implementation, in S2, the gradient temperature is set as follows: the first stage of calcination is heating from room temperature to 600°C~750°C and maintaining the temperature for 1 hour; the second stage of calcination is heating from 600°C~750°C to 950°C~1050°C and maintaining the temperature for 1 hour, wherein the heating rate is lower than 20°C / min.
[0012] In one implementation, in S4, the constant weight temperature is 950°C to 1050°C, and the heat treatment time is 30 to 60 minutes.
[0013] In one implementation, in S4, the specific operating steps of the second stage burning are the same as those in S2. After the second stage burning, weighing is performed and compared with the weighing result of the first stage. If the difference in the result does not exceed 0.3 mg, the subsequent operation is continued. Otherwise, the burning is repeated until the weight difference after two burnings does not exceed 0.3 mg.
[0014] In one implementation, in S1, the pretreatment step further includes soaking the silicon-carbon material in an oxidizing solvent for 10 to 30 minutes, and then drying it at a temperature of 70° C. to 100° C. for 2 to 4 hours.
[0015] In one implementation, in S3 and S4, the balance used for weighing is an analytical balance with an accuracy of 0.1 mg.
[0016] Beneficial effect: The method for testing the silicon content in the silicon-carbon material provided by the present invention forms a pre-oxidation layer on the surface of the silicon-carbon material by using an oxidizing solvent, and fully and quickly oxidizes the material at high temperature to generate oxides by designing different gradient temperatures, so that the oxide generation speed in the process of high-temperature testing of silicon content is faster, SiO x The generation is faster and more complete, thereby reducing the time cost of testing and improving the test efficiency of industrial testing of Si content in silicon-carbon materials, providing a method for testing the silicon content in silicon-carbon materials with a shorter test cycle, higher stability and higher safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a flow chart of the steps of the method for testing the silicon content in the silicon-carbon material provided by the present invention; Figure 2 This is a sample image of the silicon-carbon material provided in Example 1 after the first stage of burning; Figure 3 This is a sample image of the silicon-carbon material provided in Example 1 after the second stage of burning; Figure 4 is a SEM image of the silicon-carbon material after calcination provided in Example 1; Figure 5 is a SEM image of the silicon-carbon material after calcination provided in Example 1; Figure 6 is an EDS image of the silicon-carbon material after calcination provided in Example 1; Figure 7 is the XRD pattern of the silicon-carbon material after calcination provided in Example 1; Figure 8 This is the temperature-mass percentage change diagram of silicon-carbon material after TG.
[0018] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0020] Read more Figure 1 , Figure 1 The present invention provides a method for testing the silicon content in a silicon-carbon material, which specifically comprises the following steps: S1. Provide a silicon-carbon material, perform pretreatment, mix an oxidizing solvent on the surface of the silicon-carbon material, coat an oxide layer, and obtain a material to be tested; S2, transferring the material to be tested into a crucible, placing the crucible into a heating device at room temperature, and setting a gradient temperature for the first stage of burning; S3, transferring the heated crucible to a dryer, cooling it to room temperature and weighing it; S4. Re-burn the crucible and the material to be tested after the burning in the second stage, so that the material to be tested is in a constant weight state, and the silicon content in the silicon-carbon material is calculated by weighing the result.
[0021] Specifically, in S1, the oxidizing solvent includes any one of hydrogen peroxide, sodium hypochlorite and iodine. Accurately weigh 1±0.05g of the sample, transfer it to a pre-calcined crucible and record the mass of the empty crucible m0, the sample mass m1 and the total crucible mass m2 after pretreatment respectively. At the same time, weigh an equal amount of oxidizing solvent in the crucible and conduct a synchronous experiment as a blank group experiment to record the mass. In addition, in S1, the pretreatment step can further include soaking the silicon-carbon material in the oxidizing solvent for 10 to 30 minutes, and then drying it at a temperature of 70°C to 100°C for 2 to 4 hours.
[0022] In S2, the heating device is a muffle furnace or a box-type atmosphere furnace. The gradient temperature is set as follows: the first stage of calcination is heating from room temperature to 600°C~750°C and keeping the temperature constant for 1 hour; the second stage of calcination is heating from 600°C~750°C to 950°C~1050°C and keeping the temperature constant for 1 hour, wherein the heating rate is less than 20°C / min.
[0023] In S3 and S4, the balance used for weighing is an analytical balance with a precision of 0.1 mg.
[0024] Specifically, in S4, the constant weight temperature is 950°C to 1050°C, and the heat treatment time is 30 to 60 minutes. Record the weight of the crucible m3 after cooling to room temperature. Furthermore, the specific operation steps of the second stage of calcination are the same as those in S2. After the second stage of calcination, weigh and compare with the weighing results of the first stage. If the difference in the results does not exceed 0.3 mg, continue the subsequent operation, otherwise repeat the calcination until the weight difference after two calcinations does not exceed 0.3 mg. Record the mass after constant weight as m4.
[0025] The calculation formula for the silicon content in the silicon-carbon material is calculated by weighing the result: Wsi= 0.08 00%; Among them, 60.08 is the relative molecular mass of silicon dioxide, 28.09 is the relative molecular mass of silicon, m 4(空白) is the constant weight of the blank group after two burnings, m 0(空白) is the mass of the empty crucible after pretreatment.
[0026] The present invention provides several embodiments below to illustrate the technical solution provided by the present invention. S1. Provide different oxidizing solvents to mix on the surface of the silicon-carbon material to coat an oxide layer to obtain a material to be tested.
[0027] S2. Weigh 1±0.05g of the processed silicon-carbon material sample, spread it flat and transfer it to a crucible for the first stage of heating and calcining, calcine it to 600℃~750℃, calcine it for 1 hour, take it out, and after cooling it, the silicon-carbon material sample powder changes from black-gray powder to yellow-brown powder. That is, at this time, most of the C in the silicon-carbon material powder is converted into CO / CO2 gas and discharged, and Si is converted into SiO / SiO2, but its purity is low, and the impurities are not completely removed, so it appears as brown-yellow powder. Figure 2 , Figure 2 This is a sample picture of the silicon-carbon material provided in Example 1 after the first stage of burning.
[0028] S3. Place the crucible after burning back into the muffle furnace or atmosphere box furnace for the second stage of heating to 1000℃. After keeping the temperature constant for 1 hour, take it out and wait for it to cool down before observing the state of the material. The purity of SiO2 after burning is relatively high, and white SiO2 powder will appear after its impurities and volatile substances are removed. Figure 3 , Figure 3 This is a sample picture of the silicon-carbon material provided in Example 1 after the second stage of burning.
[0029] S4. Keep the material at a constant weight of 1000°C for 30 minutes, take it out and weigh it after cooling, and record the mass of the sample crucible.
[0030] The specific implementation conditions and data results are shown in Tables 1 to 4.
[0031] Table 1. Test results of silicon content in silicon-carbon materials of different crucible qualities Among them, in the preparation conditions of the embodiments in the table of Table 1, the temperature gradient is 25°C-600°C-1000°C, and the oxidizing solvent is hydrogen peroxide.
[0032] Table 2. Data comparison between the method provided by the present invention and the existing TG and ICP methods Table 3. Comparison of data results of the same oxidizing solvent under different temperature gradients Among them, in the preparation conditions of the examples in the table of Table 3, the oxidizing solvent is hydrogen peroxide.
[0033] Table 4. Comparison of data results of silicon-carbon materials in different oxidizing solvents.
[0034] Among them, in the preparation conditions of the embodiments in the table of Table 1, the temperature gradient is 25°C-600°C-1000°C.
[0035] Combined with the data results in Tables 1 to 4, and Figure 4~Figure 8 ,in, Figure 4 is a SEM image of the silicon-carbon material after calcination provided in Example 1, Figure 5 is a SEM image of the silicon-carbon material after calcination provided in Example 1, Figure 6 This is the EDS image of the silicon-carbon material after calcination provided in Example 1. Figure 7 is the XRD diagram of the silicon-carbon material after calcination provided in Example 1, Figure 8 This is the temperature-mass percentage change diagram of the silicon-carbon material after TG. It can be seen that the constant weight silicon-carbon material has completed the reaction after calcination.
[0036] In summary, the method for testing the silicon content in the silicon-carbon material provided by the present invention forms a pre-oxidation layer on the surface of the silicon-carbon material by using an oxidizing solvent, and fully and quickly oxidizes the material at high temperature to generate oxides by designing different gradient temperatures, so that the oxide generation speed in the process of high-temperature testing of the silicon content is faster, SiO x The generation is faster and more complete, thereby reducing the time cost of testing and improving the test efficiency of industrial testing of Si content in silicon-carbon materials, providing a method for testing the silicon content in silicon-carbon materials with a shorter test cycle, higher stability and higher safety.
[0037] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for testing the silicon content in a silicon-carbon material, characterized in that: The specific steps include: S1. Provide a silicon-carbon material, perform pretreatment, mix an oxidizing solvent on the surface of the silicon-carbon material, coat an oxide layer, and obtain a material to be tested; S2, transferring the material to be tested into a crucible, placing the crucible into a heating device at room temperature, and setting a gradient temperature for the first stage of burning; S3, transferring the heated crucible to a dryer, cooling it to room temperature and weighing it; S4. Re-burn the crucible and the material to be tested after the burning in the second stage, so that the material to be tested is in a constant weight state, and the silicon content in the silicon-carbon material is calculated by weighing the result.
2. The method for testing silicon content in silicon-carbon material according to claim 1, characterized in that: In S1, the oxidizing solvent includes any one of hydrogen peroxide, sodium hypochlorite and iodine.
3. The method for testing silicon content in silicon-carbon material according to claim 1, characterized in that: In S2, the heating device is a muffle furnace or a box-type atmosphere furnace.
4. The method for testing the silicon content in the silicon-carbon material according to claim 1, characterized in that: In S2, the gradient temperature is set as follows: the first stage of calcination is heating from room temperature to 600°C~750°C and maintaining the temperature for 1 hour; the second stage of calcination is heating from 600°C~750°C to 950°C~1050°C and maintaining the temperature for 1 hour, wherein the heating rate is lower than 20°C / min.
5. The method for testing silicon content in silicon-carbon material according to claim 1, characterized in that: In S4, the constant weight temperature is 950°C to 1050°C, and the heat treatment time is 30 to 60 minutes.
6. The method for testing silicon content in silicon-carbon material according to claim 1, characterized in that: In S4, the specific operation steps of the second stage burning are the same as those in S2. After the second stage burning, weighing is performed and compared with the weighing result of the first stage. If the difference in the result does not exceed 0.3 mg, the subsequent operation is continued. Otherwise, the burning is repeated until the weight difference after two burnings does not exceed 0.3 mg.
7. The method for testing silicon content in silicon-carbon material according to claim 1, characterized in that: In S1, the pretreatment step further includes soaking the silicon-carbon material in an oxidative solvent for 10 to 30 minutes, and then drying it at a temperature of 70° C. to 100° C. for 2 to 4 hours.
8. The method for testing silicon content in silicon-carbon material according to claim 1, characterized in that: In S3 and S4, the balance used for weighing is an analytical balance with a precision of 0.1 mg.
Citation Information
Patent Citations
Method for testing content of silicon in nano silicon-based material
CN111122373A